Transition to “green economy” in Uzbekistan: Opportunities and challenges - Rashidova Odina (Zien Journals, 2025)
This article examines the necessity and strategic directions of transitioning to a green economy in Uzbekistan. It analyzes the environmental, economic, and social challenges associated with traditional growth models and highlights the urgency of adopting sustainable development principles. The study emphasizes the importance of modernizing production processes, promoting renewable energy sources, and implementing environmental policy reforms. Special attention is given to national programs and international cooperation aimed at fostering ecological sustainability and green innovation. The paper concludes that a gradual but determined shift to a green economy is essential for ensuring long-term economic resilience and environmental protection in Uzbekistan.
Keywords: green economy; sustainable development; environmental policy